Precise electrical detection of the field and current-induced switching mode of a magnetic nanodisk in a non-local spin valve. (16th June 2021) - Reeve, R M; Pfeiffer, A; Kläui, M; Zhand, G; Attané, J P; Vila, L
Abstract: In this work, we study the manipulation and the detection of the magnetic state and switching modes of a Permalloy disk, using a non-local spin-valve with dual CoFe injectors and with the disk acting as the detector electrode. Applying simultaneously external magnetic fields and spin currents from the injectors, we demonstrate the possibility to use the spin torque created by the spin current to modulate the switching modes and switching fields of the disk, following the disentanglement of the influence of Joule heating. Moreover, by engineering the device to have a very small overlap of the spin conduit with one side of the disk, we demonstrate how, with the help of a first-order reversal curve analysis, we can extract the precise details of the switching from the monodomain to the vortex state, including the chirality of the system without the need for direct imaging.